Tribological Characterization of TiN Coatings Prepared by Sputtering. (2016) - Chavda, Mahesh R.; Dave, Divyesh P.; Chauhan, Kamlesh V.; Rawal, Sushant K.
Abstract: The aim of this paper is to study tribological properties of titanium nitride (TiN) coating deposited on various substrates by DC magnetron sputtering technique. The DC power of metallic titanium target was varied from 200 to 350 W at an increment of 50W. The effect of power variation on structure and surface morphology was characterized by X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM). The tribological properties of coating were investigated using pin on disk apparatus. TiN coating exhibited a higher wear resistance and low coefficient of friction compared to uncoated substrates of mild steel, aluminum and brass.